Bilateral trade agreements and the world trading system - Jayant Menon (Asian Development Bank Institute (ADBI), 2006)
The interest in forming BTAs has been growing at a phenomenal rate. In the Asia-Pacific region alone, the number of BTAs has more than tripled over the past 5 years, from 57 in 2002 to 176 in October 2006. There are more than 300 worldwide. In this paper, we try to explain the proliferation of BTAs by identifying the underlying motivations behind them. We identify a set of general and specific factors involved. The general factors related to disenchantment with progress of the WTO; snowballing and domino effects as a result of countries not wanting to be left behind; lower visibility and thus lower resistance from opposing forces; and pure politics driven directly by politicians or political parties. There are three broad categories of specific factors that we identify: economic; strategic and event driven. Each are further divided into sub-categories and in total we identify 11 specific factors to explain the proliferation of BTAs. Next we look at the impact of BTAs on multilateralism and the world trading system. In general, it is would appear that the sheer number of BTAs and their continued rapid growth is fragmenting the world trading system. The most obvious effect is the much discussed spaghetti-bowl effect. It is also distracting, and drawing scarce resources away from the multilateral effort. But the story is not that simple or straight-forward once we consider specific factors. The fallacy of division applies because the motivation in pursuing a BTA can determine if its impact on the world trading system is positive or negative. Most of the event driven BTAs appear to either support multilateralism or have a positive effect on the world trading system. All of the strategically motivated BTAs appear to have a negative effect. Of the economically motivated BTAs, sector expanding and market restoring BTAs have the potential of supporting the multilateral process, while market creating and sector excluding BTAs appear to threaten it. Finally, we look at what the future might hold. Are BTAs likely to continue proliferating? It seems that they will until the world trading system is so distorted that countries will be forced to seek a remedy. This response may take several forms. One is the consolidation of BTAs into region-wide PTAs, or blocks, where the various BTAs between members belonging to the same region become largely redundant. For instance, an Asia-wide FTA would supersede a host of regional BTAs and consolidate them into one region-wide agreement. Although this may reduce the number of intra-regional BTAs, it may serve to further fragment the world trading system by carving it up into distinct regional blocks. Furthermore, it may provide fresh impetus for a new wave of market restoring BTAs as traditional trade partners outside the region seek to retain trade access with members of the consolidated PTA. In fact, with more countries outside the region that inside, it is possible that the total number of BTAs could actually increase. Thus, consolidation through region-wide PTAs is not the remedy to the problems facing the world trading system. The second response may come in the form of the completion of the Doha round with minimum compromises. A bona fide conclusion to the Doha Round should dilute preferences that are currently scattered around the world, and take away much of the incentive to continue pursuing BTAs. If this happens, then the proliferation of BTAs would have contributed to their eventual demise, in terms of their impact on the world trading system. This is much more like a remedy to the problems facing the world trading system. But what is the Doha round fails, or is concluded in such a watered-down form that its impact is minimal? Although this may provide an additional incentive to pursue more BTAs and PTAs, there may eventually come a point where countries may voluntarily seek a remedy that lies in their own best interests. Not only is the cost of administering and implementing multiple country-specific BTAs high, it rises with the number of BTAs. Once a country has concluded BTAs with most of its major trading partners, it makes sense to: equalize preferences across these BTAs and offer them to non-BTA countries on an MFN basis. This would remove the administrative burden, and eliminate distortions to country and global trade patterns. As it is with reversing much of second-best policies, it is the actual realized cost of implementation rather than any potential unrealized benefits that usually drives the process. And there are significant potential unrealized benefits that will accrue to the country concerned as well as the world trading system if this process of multilateralizing preferences is pursued, whatever the reason.
Keywords: 330